2009
DOI: 10.1111/j.1749-6632.2009.04675.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐C1q Antibodies in Juvenile‐Onset Systemic Lupus Erythematosus

Abstract: The objective of this study was to evaluate the presence of anti-C1q antibodies Hospital Israelita Albert Einstein Research Institute, São Paulo, Brazil in 67 juvenile systemic lupus erythematosus (JSLE) patients and 26 healthy controls and to assess the association of these antibodies with disease activity, nephritis, and presence of anti-double-stranded (ds)DNA. Anti-C1q antibodies were detected by ELISA. A higher frequency of anti-C1q antibodies was observed in JSLE patients compared to controls (20% vs. 0%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 20 publications
2
25
0
4
Order By: Relevance
“…Rosen and co-workers suggested that a considerable number of lupus autoantigens were clustered within apoptotic blebs [49,50]. This condition is further compounded by the presence of anti-C1q autoantibodies detected in the sera of a number of patients suffering from SLE [51][52][53][54][55]. The CRT binds to the CD91 and C1q, which is known to bind to the CRT through its collagenous "tail", forms a complex with CRT/CD91.…”
Section: Clearance Of Apoptotic and Necrotic Cells Via C1qmentioning
confidence: 99%
“…Rosen and co-workers suggested that a considerable number of lupus autoantigens were clustered within apoptotic blebs [49,50]. This condition is further compounded by the presence of anti-C1q autoantibodies detected in the sera of a number of patients suffering from SLE [51][52][53][54][55]. The CRT binds to the CD91 and C1q, which is known to bind to the CRT through its collagenous "tail", forms a complex with CRT/CD91.…”
Section: Clearance Of Apoptotic and Necrotic Cells Via C1qmentioning
confidence: 99%
“…Though, various studies have shown relationships between complement consumption and SLE disease activity, most have been done in adults [22][23][24]. Studies in children with LN are limited and restricted to the analysis of individual parameters [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, researchers have used clinical-laboratory information and human biological samples collected by this facility, resulting in a series of works. 3,4,[8][9][10][11][12][13][14][15] Therefore, as a pioneer initiative, this clinical-laboratory database and biorepository will supply researchers with important information and an apparatus that can illuminate the causative factors of autoimmune diseases and primary immunodeficiencies. …”
Section: Introductionmentioning
confidence: 99%